Sustainable Development Goal 4 on Quality Education for All: How Does the Philippines Fare and What Needs to Be Done? - Jose Ramon G. Albert; Lovelaine B. Basillote; Jason P. Alinsunurin; Jana Flor V. Vizmanos; Mika S. Mu\~noz; Angelo C. Hernandez (Philippine Institute for Development Studies (PIDS), 2023)
The Global Goal on ensuring inclusive and equitable quality education and promoting lifelong learning opportunities for all promotes equality in access to quality learning, supports economic development, improves health outcomes, empowers women and girls, and fosters global citizenship and peace. By reducing inequities in education, both in terms of access and quality, we can help to build a more equitable, prosperous, and sustainable world. This study provides a detailed examination of the progress of the Philippines in achieving Sustainable Development Goal 4 (SDG4) on quality education and lifelong learning opportunities for all. It sets the stage by outlining the Philippine educational policy landscape, including its legal and institutional frameworks. The analysis then progresses to a target-bytarget review of SDG 4, highlighting the nation's accomplishments and ongoing challenges. Notable achievements include nearly universal primary education enrollment and increased secondary education participation. However, issues like high dropout rates and subpar learning outcomes remain. The Philippines has also seen growth in early childhood development (ECD) and pre-primary education enrollments, yet access for disadvantaged children is still limited. The country has policies to enhance access to affordable technical, vocational, and higher education, but the quality of these programs and their alignment with future skills needs improvement. Inclusive education initiatives exist, such as programs for learners with disabilities and indigenous communities, but challenges in ensuring universal quality education persist. A shift in education outcomes in favor of girls is observed, with boys now more likely to drop out than girls across various educational levels, and with girls doing better than boys in learning. While literacy rates appear high, the need to redefine literacy measurements, considering issues like digital skills, is evident. Progress in school infrastructure development is significant, especially with the K-12 rollout, but enhancing learning environments, including using technology for learning, remains crucial. The Philippines boasts a large teaching workforce, yet there is a pressing need to elevate teacher training quality and align it with future skill requirements. The study pinpoints critical improvement areas, including addressing learning deficits' root causes, implementing an open data policy, and refining teacher training and workload. Concluding with a call to action, the study underscores the necessity of a comprehensive strategy to tackle educational challenges holistically, with integrated planning among the three main government agencies tasked to manage the sector. It suggests developing specific targets for inclusive quality education. This comprehensive review offers valuable insights and practical recommendations for stakeholders, aiming to ensure the Philippines fulfills its commitment to quality education for all by 2030.
Keywords: 330; education; basic education; higher education; TVET; quality education